DOI: 10.17077/etd.9mkkvyzi
|View full text |Cite
|
Sign up to set email alerts
|

Drug transporters in the nasal epithelia and their contribution in drug delivery

Abstract: I sincerely appreciate all the help and support from my family and friends in Jordan and Egypt and the ones I met in Iowa. Finally, my parents, my brother Ziad and sister Haneen, I would like to thank them all for their love and never ending support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 96 publications
1
18
0
Order By: Relevance
“…12, 13 Investigations of uptake transporter activities have also used Western blotting and immunohistochemistry to confirm the expression of OCT2, OCTN2, LAT1, LAT2, CNT3, and ENT1 in cows. 10, 12, 1416 Further in vivo investigations have shown that OCT2 and OCTN2 are able to modulate the transfer of drugs across the nasal mucosa and the activity of these transporters significantly enhances nose to brain transport of substrate drug compounds.…”
Section: Introductionmentioning
confidence: 99%
“…12, 13 Investigations of uptake transporter activities have also used Western blotting and immunohistochemistry to confirm the expression of OCT2, OCTN2, LAT1, LAT2, CNT3, and ENT1 in cows. 10, 12, 1416 Further in vivo investigations have shown that OCT2 and OCTN2 are able to modulate the transfer of drugs across the nasal mucosa and the activity of these transporters significantly enhances nose to brain transport of substrate drug compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For example, FLT is reported to be a substrate for at least 4 nucleoside transporters, two of which are known to be expressed in the nasal mucosa. (21, 25) Based on the reported substrate interactions of other nucleoside-like drug compounds, additional transporters, especially efflux transporters may also play an important role in determining the overall distribution of intranasally administered compounds. The evaluation of in vivo disposition patterns is complicated by the activity of a variety of transporters, some identified and others unknown, on distribution, along with a lack of information regarding exact tissue concentrations and target concentrations that result in the saturation of a transporter.…”
Section: Discussionmentioning
confidence: 99%
“…(20) ENT1 and CNT3 have been demonstrated to be expressed in the nasal mucosa and are present primarily on the apical surface of the respiratory and olfactory epithelia in the nasal cavity. (9, 21) Using cell-based techniques, Paproski, et al demonstrated that alovudine (FLT analog) was a substrate for ENT1, ENT2, CNT1 and CNT3. (22) The equilibrative transporters were also shown to have lower affinities but greater capacities for alovudine transport than the concentrative nucleoside transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Another proposed pathway for drug absorption after intranasal administration is the direct transport of drugs to the CNS known as "nose-to-brain delivery" via the olfactory and trigeminal nerves 17 . It was observed early in the last century that viruses like poliomyelitis and stomatitis can enter to the brain via the nose 16,18 . Later, this pathway was reported in a study by Reiss et al who showed that stomatitis virus can enter to the brain via the olfactory nerves 19 .…”
Section: VImentioning
confidence: 99%
“…In addition, the volume of the nasal cavity limits the volume of the dose that can be administered to ~ 100-150 μl. While absorption from the nasal cavity does bypass hepatic first pass metabolism, the activity of the metabolizing enzymes found in the nasal mucosa can also decrease the amount of drug available for uptake 16 .…”
Section: VImentioning
confidence: 99%